Spatiotemporal localizations of light in quadratically nonlinear media with transversal inhomogeneity. Issue 1 (January 2021) - Chuprikov, Ivan; Kalinovich, Aleksey; Komissarova, Maria; Sazonov, Sergey; Zakharova, Irina
Abstract: In the current study with the help of mathematical modeling we investigate the generation of second optical harmonic provided various group velocity dispersion (GVD) and third order dispersion effects taken into account. Varying values and signs of the third-order dispersion at quasi-zero values of GVD we reveal the conditions of light bullet formation and stable propagation. To this end we use a generalization of the well-known system of the second harmonic generation in quasi-optical approach. Particular attention is paid to the case when GVD at the second harmonic is close to zero. In addition, we investigate these cases using both focusing and defocusing waveguide which means the presence of transversal inhomogeneity.